Pengaruh Matos terhadap Peningkatan CBR (California Bearing Ratio)dan Sifat Kedap Airpada Tanah Sekitar Rawa Pening - Erwin Harris Saputra; Lie Sanders Deckcrealy; Djoko Suwarno; Budi Setiyadi (G-SMART, 2018)
Rawa Pening soil contains peat has low level of California Bearing Ratio (CBR) and high permeability so it is less suitable for embankment. Above the embankment functioned as a road body. This study adds cement and matos (normal) to increase soil bearing capacity. (50%), 50% G 50% Cement (C) 8%, TSRP 50% + G 50% + C 8% + Matos (M) 2%, 4% and 6%. CBR soaked, normal results obtained CBR 2.99% while the CBR requirement of 5.44%. Addition of C 8% adds CBR value to 9,25%, while addition of M 2% increase CBR value equal to 8,9%, M 4% yield CBR become 16% and M 6% get CBR equal to 16%. Low compaction, normal soil undergoes seepage after a day, compaction is undergone seepage after 3 days and standard compaction does not undergo seepage for 7 days. The most optimal result, with stabilization of C 8% and M 4%. Addition of M 2% is not effective or equal to 8% cement. The addition of M 6% equals M 4%.